Pain-Related White-Matter Changes Following Mild Traumatic Brain Injury: A Longitudinal Diffusion Tensor Imaging Pilot Study - Ho-Ching Yang; Tyler Nguyen; Fletcher A. White; Kelly M. Naugle; Yu-Chien Wu (Diagnostics)
Background: This study used diffusion tensor imaging (DTI) to detect brain microstructural changes in participants with mild traumatic brain injury (mTBI) who experienced post-traumatic headaches, a common issue that affects quality of life and rehabilitation. Despite its prevalence, the mechanisms behind post-traumatic headache are not well understood. Methods: Participants were recruited from Level 1 trauma centers, and MRI scans, including T1-weighted anatomical imaging and DTI, were acquired 1 month post-injury. Advanced imaging techniques corrected artifacts and extracted diffusion tensor measures reflecting white-matter integrity. Pain sensitivity assays were collected at 1 and 6 months post-injury, including quantitative sensory testing and psychological assessments. Results: Significant aberrations in axial diffusivity in the forceps major were observed in mTBI participants (n = 12) compared to healthy controls (n = 10) 1 month post-injury (p = 0.02). Within the mTBI group, DTI metrics at 1 month were significantly associated with pain-related and psychological outcomes at 6 months. Statistical models revealed group differences in the right sagittal stratum (p < 0.01), left insula (p < 0.04), and left superior longitudinal fasciculus (p < 0.05). Conclusions: This study shows that DTI metrics at 1 month post-injury are sensitive to mTBI and predictive of chronic pain and psychological outcomes at 6 months.